Parkinson, chaos & quantum computing - Suda Neto, Jogi [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Signal processing models and artificial intelligence algorithms have benefited from the advance of Quantum Computing. Nevertheless, just modest possibilities have been seen in that sense for speech and voice analysis. Thus, the intention of the author of this dissertation is to investigate whether Quantum Machine Learning models might perform well in classifying Parkinsonian speech. Particularly, since the speech database used in the experiments produced just a few features, available current quantum models are feasible for the proposed approach. The results, up to this point, stimulate further investigation and suggest prominent perspectives.

Modelos de processamento de sinais e algoritmos de inteligência artificial se beneficiaram com o avanço da Computação Quântica. No entanto, apenas possibilidades modestas foram vistas nesse sentido para a análise da fala e da voz. Assim, a intenção do autor desta dissertação é investigar se os modelos de Aprendizado de Máquina Quântica podem ter um bom desempenho na classificação da fala parkinsoniana. Particularmente, como o banco de dados de fala utilizado nos experimentos contém poucas características, os modelos quânticos atuais disponíveis são viáveis para a abordagem proposta. Os resultados, até aqui, estimulam futuras investigações e sugerem perspectivas proeminentes.
Parkinson, caos & computação quântica
Keywords: Quantum machine learning; Parkinson’s disease; Digital signal processing; Voice analysis; Aprendizado de máquina quântica; Doença de Parkinson; Processamento de sinais digitais; Análise de voz